A Comparative Study between Ketamine and Lidocaine or Decrease Propofol Injection Pain During Induction of Anesthesia - Khadka, Bikash; Sharma, Nil Raj (Birat Journal of Health Sciences, 2021)
Introduction: Pain during the injection of anesthetic agents may be distressing and can reduce the acceptability of an otherwise useful agent such as propofol during daycare surgeries. Lidocaine and ketamine both are used as pre-treatment to decrease propofol induced pain. This study aims to compare the effectiveness of ketamine injection to decrease propofol-induced pain in comparison to lidocaine injection. Methodology: This is a prospective cross-sectional comparative study. Eighty-nine cases were divided into two groups where group K received ketamine 2 ml (0.2 mg/kg) whereas group L received lidocaine 2% 2ml (0.5 mg/kg) after venous occlusion with rubber tourniquet. One-fourth dose of propofol was injected 1 min after release of tourniquet and pain accessed at 0, 1, and 2 minutes of propofol injection with a verbal response and behavioral signs. Chi-square test and paired T-test were used and a p-value less than 0.05 was considered significant. Result: Regarding hemodynamic, oxygenation, and adverse effects there was no significant difference. Immediately after propofol injection, only 1 patient of the ketamine group had mild pain (2.22%) while 12 patients from the lignocaine group had mild pain (27.27%) with a p-value of 0.009. Also after 2 minutes of propofol injection, only 12 cases had mild pain i.e. 13.48% (1 from ketamine group i.e. 2.22% and 11 from lidocaine group i.e. 25%) with p-value of 0.002. Conclusion: Our study helps prove low-dose ketamine is more effective in reducing the incidence and severity of pain on injection of propofol in comparison to Lidocaine with better hemodynamic stability.